The Effect Of Leg Muscle Strength Exercise On The Intensity Of Prelansian And Elderly Knee Pain In The Village Of Pandean Lamper, Semarang - Wahyu Puspitasari; Shinta Eka Kartika; Metta Christina (Sean Institute, 2023)
Studies using effective treatment/medication options for treating knee pain such as stretching, physiotherapy in the form of infrared, tens, neuromuscular taping, elderly exercise, medication and even surgery, it turns out that many patients do not experience long-term recovery from this treatment. So the formulation of the problem in this study is how to influence leg muscle strength training to treat knee pain.The purpose of this study was to determine the effect of leg muscle strength training to treat knee pain.This research uses quantitative research, the research design uses Pre-Experimental using One Group Pre-Test Post-Test Design. The population in this study were residents of Pandean Lamper Village aged 45 years and over who had experienced knee pain. The number of research samples was 31 people with a purposive sampling technique. The independent variable in this study was leg muscle strength training, the dependent variable was the intensity of knee pain. Data collection time for 6 weeks. The instruments used were Numerical Rating Scale pain scales and observation sheets. The statistical test used in this study was the Wilcoxon signed ranks test.The results of the Wilcoxson different test showed a sig value of 0.000 <0.05, this means that there was a significant difference between the results of the pre-test and post-test. So that it can be said that there is an effect of muscle strength training on the intensity of knee pain in pre-elderly and elderly people in the Pandean Lamper sub-district.The conclusion of this study is that pre-elderly and elderly people who experience knee pain should exercise with weights with special movements to train leg muscle strength which is done at least 2x a week to reduce pressure on the knee joints and can also reduce the intensity of knee pain.Suggestions that can be given are that pre-elderly and elderly people should choose or add to their type of exercise with weight sports or exercise to train leg muscle strength so that the leg muscles strengthen, the pressure on the knee joint is reduced so that the knee pain disappears. Finally able to do activities better in the future.